Echinococcus across the north : Current knowledge, future challenges - Davidson, Rebecca K.; Lavikainen, Antti; Konyaev, Sergey; Schurer, Janna; Miller, Andrea L.; Oksanen, Antti; Skírnisson, Karl; Jenkins, Emily (Food and Waterborne Parasitology, 2018)
Abstract Zoonotic Echinococcus spp. cestodes are present in almost all circumpolar nations, and have historically posed a risk to health of indigenous as well as other northern residents. However, surveillance data on both alveolar (AE) and cystic (CE) echinococcosis remains incomplete throughout the circumpolar region: Russia, Fennoscandia, Iceland, Greenland, Canada and Alaska (USA). Prevalence of Echinococcus spp. varies considerably in definitive canid hosts, animal intermediate hosts and accidental hosts like humans. Yet despite the high prevalence reported in canids in some geographic locations, human AE and CE are much less common than in endemic Asian and central European countries. This paper explores knowledge gaps and future challenges posed by Echinococcus spp. in eight circumpolar countries, a region where rapid environmental and social change are rewriting the boundaries, transmission, and impact of many pathogens, including zoonotic Echinococcus spp. Genotypes G6, G8 and G10 of Echinococcus canadensis are causative agents of human CE and have been identified in sylvatic (wild animal) and synanthropic (ecological association with humans) cervid-canine life cycles in the following northern regions: Alaska and northern Canada - G8 and G10; northern Russia - G6, G8, G10; and Fennoscandia - G10 in Finland - with no recent reports from Norway or Sweden. Echinococcus multilocularis, which causes AE, has been identified in a sylvatic arvicoline rodent-canine lifecycle in Alaska, Canada, Russia, Sweden and Svalbard (Norway). Asian, Mongolian, European and North American strains of E. multilocularis are found in Russia, with the North American N1 strain predominating in the north. The N1 strain is also found in Alaska, as well as Svalbard, whilst Asian strains have been identified in western Alaska. Central North American (N2) strain and European-type strains of E. multilocularis are present in Canada. Typing of the strain in Sweden is still pending. Individual human cases of AE with N2 and European-type ...